Why do young people tag photos on social networking sites? Explaining user intentions. Issue 1 (February 2018) - Dhir, Amandeep; Kaur, Puneet; Rajala, Risto
Highlights: The study investigated the reasons behind why people keep tagging on social media using extended UTAUT2 model. Determinants of user intention to use a specific social media feature were examined with 780 social media users. Habit and hedonic motivation have significant influence on intentions to photo-tag. Self-efficacy, Social Status, Influence and Presence had insignificant influence. Facilitating conditions, Effort and Performance expectancy has no influence. Abstract: Scholars have emphasized an urgent need to investigate the determinants of user intentions to share content on social networking sites (SNS). A growing share of the content in social media is visual − including Photos − which users can share by tagging. To improve the understanding of the determinants of social media users' behavioral intention to share content, this study investigates why people tag photos on SNS. A comprehensive research model was developed based on the Unified Theory of Acceptance and Use of Technology (UTAUT2) and Social Cognitive Theory (SCT). The validity of the extended UTAUT2 model was tested on a new form of technology use which is not only timely but is much desired by the scholars engaged in information systems research. The research model investigates the role of habit, hedonic motivation, facilitating conditions, social influence, effort expectancy, performance expectancy, social presence, social status, and self-efficacy in influencing the user intentions to engage in photo-tagging. The research model was tested using a cross-sectional study of 780 adolescent Facebook users. The findings suggest that only habit and hedonic motivation have a significant direct influence on the user's intentions to tag photos. The study contributes to the theorizing of the role of habits and hedonic motivations in user behaviors in the SNS and provides new insights into these factors for the managers of social media sites.